Great sin and the heresies of Eutyches. Mysterious description of the conquest of Dalmatia in the Chronicle of the Orthodox Priest of Dioclea - Kowalski, Wawrzyniec (Balcanica Posnaniensia. Acta et studia, 2019)
The theme of the conquest of Dalmatia by the Goths and their leaders: Totila and Ostroyllus is one of the most extensive and most important narratives within the Chronicle of the Priest of Dioclea. The article discusses the link between this theme and the Dalmatian tradition. It shows how some fragments of the medieval historiography of the region indicate that the legend of the invasion existed earlier than the Chronicle and could have been linked to the story of the assassination of the Croatian king, which we know i. a. from the Croatian version the Chronicle and from the Hungarian-Polish Chronicle. On this basis, some differences between the Latin and the Croatian versions of the Chronicle of the Priest of Dioclea are highlighted and in this context possible origins of the words about the great evil among Christians and about the Eutychian heresy have been given their possible explanation.